1984
DOI: 10.1021/ja00326a014
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer from aromatic hydrocarbons and their .pi.-complexes with metals. Comparison of the standard oxidation potentials and vertical ionization potentials

Abstract: The energetics of electron transfer from an extensive series of alkyl-substituted benzenes are measured both in solution and in the gas phase. The standard oxidation potentials stem from the reversible cyclic voltammograms (CV) in trifluoroacetic acid using the recently developed microvoltammetric electrodes. These values show an excellent correlation with the vertical ionization potentials 7p of the same aromatic hydrocarbons in the gas phase. Thermochemical analysis indicates that the slope of less than unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
170
1
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(188 citation statements)
references
References 1 publication
15
170
1
2
Order By: Relevance
“…The PES values used here, along with the ab initio values that they replace, are listed below for all affected molecules. o-Xylene and m-xylene: For the highest-lying molecular orbital, B = 8.56 eV [29] replaced the theoretical CCSD(T) value of 8.70 eV.…”
Section: Experimental Orbital Binding Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The PES values used here, along with the ab initio values that they replace, are listed below for all affected molecules. o-Xylene and m-xylene: For the highest-lying molecular orbital, B = 8.56 eV [29] replaced the theoretical CCSD(T) value of 8.70 eV.…”
Section: Experimental Orbital Binding Energiesmentioning
confidence: 99%
“…p-Xylene: For the HOMO, B = 8.44 eV [29] replaced the theoretical CCSD(T) value of 8.58 eV. Styrene: For three highest orbitals, values of B/eV = 8.49, 9.27, and 10.55 [30] replaced the corresponding theoretical values of 8.56 [CCSD(T)], 9.22 (P3), and 10.71 (P3).…”
Section: Experimental Orbital Binding Energiesmentioning
confidence: 99%
“…In the case of the active species 13b, a stronger oxygenation force than that of 12a is expected because the redox potential (E 0 ) is given approximately by relation E 0 ϰe homo . 27) Indeed, it was found that the oxoiron of 9 is extracted by oxidizing a proton from the Me-group of the AcO ligand and transferring to 11, as illustrated in Fig. 4.…”
Section: Stereochemistry Of the Thymine Glycol Derivative (4a)mentioning
confidence: 99%
“…Even in this case, an UME has the advantage of a reduced charge time, 22,23 which allows the study of very fast reactions, of the order of microseconds. 24 In this sense, linear voltammetry measurements 25 in resistive media 26 like the w/o MEs employed in this study, can be performed by an UME.…”
Section: Introductionmentioning
confidence: 99%
“…Even in this case, an UME has the advantage of a reduced charge time, 22,23 which allows the study of very fast reactions, of the order of microseconds. 24 In this sense, linear voltammetry measurements 25 in resistive media 26 like the w/o MEs employed in this study, can be performed by an UME.The aim of this work was to evaluate the influence of the surfactant/co-surfactant ratio on the physical-chemical characteristics of water/soybean oil w/o MEs using measurements of the hydrodynamic radius (R H ), refractive index, viscosity and electrical conductivity, as well as to study the kinetic of redox processes by using cyclic voltammetry with an UME in the presence of ferrocene as a probe. Vegetable oil analysis is usually performed by a number of analytical techniques.…”
mentioning
confidence: 99%